Papers - - Petroleum Economics - Future of State and Federal Oil Regulation - Northcutt Ely (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1936)
A year ago the petroleum code was in effect, and Congress had before it bills with powerful backing designed to extend and put on a permanent basis the Federal authority impliedly recognized in the petroleum code. Those men in the industry who were convinced of the unconstitutionality of Federal regulation, who believed in conservation, and who were seeking accomplishment of a conservation compact among the oil-producing states, were at that time encountering difficulties in bringing about such an agreement. Since then there has been a shift in the center of gravity. Today, by virtue of the Supreme Court's Schechter case decision, the petroleum code is not in existence, the industry is not operating under an oil administrator, and the Federal-control bills are not on Congress' calendar. In view of what the Supreme Court has said in the Schechter case and the Hoosac Mills case about the local character of mining and manufacturing, the problem today is not whether the Federal Government or the State Governments ought to regulate oil production, but how effective we can make the devices that are available to us under the constitution for the conservation of the nation's oil resources. The interstate oil conservation compact ratified during the past year by Texas, Oklahoma, Kansas, New Mexico, Colorado and Illinois, approved by Congress, but not yet in effect in California, is the mechanism now at work. Interstate Oil Conservation Compact What is this interstate compact? The basic theory is simple and logical. It has four elements to it. The first point is that in order to effect the maximum recovery of our oil arid gas reserves it is necessary for some governmental authority to regulate the way in which those resources are taken out of the ground, so that the reservoir energy is efficiently used, and used equitably by the various owners of the pool. Second, that the state, as distinguished from the national government, possesses the police power necessary to protect the public interest and to protect the correlative rights of the common owners of the oil pool. Third, that the state governments ought to cooperate with each other through an interstate advisory commission so that orderly production in one state is